2005
DOI: 10.1128/jvi.79.23.14489-14497.2005
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Entry by Equine Infectious Anemia Virus Utilizes a pH-Dependent Endocytic Pathway

Abstract: Previous studies of human and nonhuman primate lentiviral entry mechanisms indicate a predominant use of pH-independent pathways, although more recent studies of human immunodeficiency virus type 1 entry appear to reveal the use of a low-pH-dependent entry pathway in certain target cells. To expand the characterization of the specificity of lentiviral entry mechanisms, we have in the current study examined the entry pathway of equine infectious anemia virus (EIAV) during infection of its natural target, equine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…Our results provide strong evidence that EIAV enters cells through a low-pH-dependent mechanism and are consistent with studies performed by Jin and Montelaro (14). Several lysosomotropic agents that prevent acidification of endosomal compartments through different mechanisms, such as the weak base ammonium chloride, the carboxylic ionophore monensin, and the H ϩ -ATPase inhibitor bafilomycin A, inhibited EIAV infection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results provide strong evidence that EIAV enters cells through a low-pH-dependent mechanism and are consistent with studies performed by Jin and Montelaro (14). Several lysosomotropic agents that prevent acidification of endosomal compartments through different mechanisms, such as the weak base ammonium chloride, the carboxylic ionophore monensin, and the H ϩ -ATPase inhibitor bafilomycin A, inhibited EIAV infection.…”
Section: Discussionsupporting
confidence: 80%
“…However, EIAV particles were more infectious at low pH, suggesting the EIAV envelope conformation in the viral particle is not the same as that found on the surface of infected cells. These results are in general agreement with the conclusions drawn by Jin et al using independent experiments with a different strain of EIAV, as described in the companion paper appearing in this issue (14).…”
supporting
confidence: 82%
“…Such increased resistance to the host factor depends on the EIAV env, reminiscent of the glycoproteins derived from some HIV-1 isolates and RNA viruses such as VSV and Ebola. EIAV env has been reported to promote virus entry via a pH-dependent pathway (22), thus reinforcing the hypothesis that the endosomal uptake could provide a port of entry that is less sensitive to SERINC5 inhibition (4). It remains to be established whether resistance to SERINC5 is a general feature shared by all EIAV isolates.…”
Section: Discussionmentioning
confidence: 81%
“…BafA1 and concanamycin A are more specific and efficient than chloroquine or ammonium chloride in blocking endocytic acidification, and a cell type-specific action of these drugs was suggested previously (38). The fact that ammonium chloride and chloroquine have no effect on RRV infectivity combined with the substantial effects of BafA1 and concanamycin A suggested that although RRV entry is likely to involve endocytosis, the direct role of endosomal acidification was less clear.…”
mentioning
confidence: 94%